Analisis Kualitatif Mutu Pendidikan dan Peran Supervisi di SD Negeri 147 Pekanbaru: Penelitian - Samsinar; M. Jaya Adi Putra (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
The purpose of this study is to analyze the quality of education and the role of supervision in country SD as new 147 if viewed in qualitative terms the main focus is on how a supervision of education influences the improvement of learning, teacher professionalism, and the attainment of national standards of education. The approach to case studies is used in this study asa method to understand the problem, data is collected through interviews, observation, and documentation. Research indicates that effective supervision plays a significant role in the improvement of education, to improve the quality of learning and professional teachers in country SD as new 147, especially in learning planning, the implementation of the curriculum, and the assessments of learning. It also refers to the evaluation process in improving the quality of education, such as education services, learning, resources and results.